2013
DOI: 10.4111/kju.2013.54.9.598
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Continence Recovery Between Robot-Assisted Laparoscopic Prostatectomy and Open Radical Retropubic Prostatectomy: A Single Surgeon Experience

Abstract: PurposeTo evaluate the recovery of continence after robot-assisted laparoscopic prostatectomy (RALP) and open radical retropubic prostatectomy (RRP).Materials and MethodsWe identified 258 patients who underwent surgery by a single surgeon to treat localized prostate cancer. The patients were divided into two groups according to operative method. In group 1, 146 consecutive patients underwent RALP, and in group 2, 112 patients underwent RRP. To compare the interval until the return of urinary continence between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The postoperative erectile function outcomes for RRP, LRP, and RARP are shown in table 3 [14,16,18,20,21,22,25,30,39,43,45,50,52,54]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative erectile function outcomes for RRP, LRP, and RARP are shown in table 3 [14,16,18,20,21,22,25,30,39,43,45,50,52,54]. …”
Section: Resultsmentioning
confidence: 99%
“…The results for operative time, blood loss, blood transfusion rates, catheterisation time, hospital stay, and overall complication rates for RRP, LRP, and RALP are presented in table 2 [10,14,15,16,18,19,20,21,22,23,24,25,29,30,32,33,34,35,36,37,39,40,41,42,43,45,48,49,52,53,54,55]. …”
Section: Resultsmentioning
confidence: 99%
“…With respect to perioperative variables, pooling data of 18 studies [ 21 , 23 , 24 , 26 , 29 , 32 , 34 , 40 , 54 , 59 , 60 , 64 , 70 , 75 , 78 , 81 , 84 , 85 ] involving 54261 participants indicated that RARP has longer operative time than RRP (WMD: 39.85 minutes; 95% CI: 20.95 to 58.75; P < 0.001) (Figure 2 ). Pooling data of 13 studies [ 10 , 21 , 23 , 29 , 30 , 34 , 40 , 60 , 70 , 75 , 78 , 84 , 85 ] results showed that RARP has less intraoperative blood loss (WMD = -507.67ml; 95% CI: -633.21 to -382.12; P < 0.001) (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…these points had more influence on urethrovesical anastomosis, bladder neck reconstruction, urethral and pelvic floor blood supply. 23 Di prerro et al reported RALP was higer postoperative recovery rate than RRP. 24 Tewari et al there was a differrence in that recovey period.…”
Section: Discussionmentioning
confidence: 96%